Professionalism and the Expanding Horizons of the Information Profession: The Challenges Facing Librarians in the 21st Century - Entsua-Mensah, Clement (Ghana Library Journal, 2004)
Given the extent to which technologicaldevelopments have influenced informationwork, the greatest challenge that confrontsinformation professionals, and for thatmatter librarians, in the 21 st century is thethreat posed by the fast moving changesthat have been brought about by theseemerging technologies.